LcNAC13 Is Involved in the Reactive Oxygen Species-Dependent Senescence of the Rudimentary Leaves in Litchi chinensis - Wang, Congcong; Liu, Hao; Huang, Lijie; Chen, Houbin; Lu, Xingyu; Zhou, Biyan (Frontiers in Plant Science, 2022)
Litchi is an important woody fruit tree. Floral initiation in litchi is triggered by low temperatures. However, defective flowering is a major challenge for litchi production in times of climate change and global warming. Previous studies have shown that the reactive oxygen species (ROS) generated by methyl viologen dichloride hydrate (MV) promotes flowering. Leaves in the panicles may affect development of the inflorescence in litchi under high temperature condition. In this study, potted litchi trees were transferred to growth chambers for low-temperature (LT) and high-temperature (HT) treatments. From a previous data set of the RNA-sequencing of the ROS-treated rudimentary leaves, a NAC transcription factor encoding gene LcNAC13 were identified. By genetic transformation of LcNAC13 to Arabidopsis thaliana and tobacco, it was found that the ROS-induced senescence of the leaves was accelerated. Silencing LcNAC13 by virus-induced gene silencing (VIGS) delayed ROS-dependent senescence. Our results suggested that LcNAC13 regulate rudimentary leaf senescence. Our study provided a new target gene for the future molecular breeding of new cultivars that could flower in warmer climates.